Potential integrated farming system model in mid hill region of West Bengal situation - Mukherjee, Dhiman (Annals of Agricultural Research, 2014)
A study was conducted at Kalimpong during 2008 to 2010 to find out suitable integrated farming system (IFS) model under mid hill situation. The objective of the study was to improve the productivity, economic returns and employment generation for the family labour. The farming system comprised of poultry, piggery, and dairy along with crop. The different IFS models assessed include FS 1 Conventional cropping with crops alone; FS 2 Crop + Poultry (20); FS 3 Crop + Dairy (3 female + 1 male); FS 4 Crop + Piggery (10); FS 5 Crop + Piggery (10) + Poultry (20) + Dairy (4); FS 6 Crop + Piggery (10) + Poultry (20). Amongst all IFS models evaluated, FS 5 (Crop + Piggery (10) + Poultry (20) + Dairy (4)), was found to be the best compared to all other models for gross income (Rs 10,1482/ha), net income (Rs 24,935/ha) and sustainability index (88.5%). This model generated an employment of 193 mandays / year. The FS 6 (Crop + Piggery (10) + Poultry (20)), was the second best IFS model. Hence these IFS models may be adopted in the mid hill region of West Bengal.